(untitled) (Global Journal of Science Frontier Research, 2024)
It is in a strategic location in the Far East and Southeast Asia a maritime route making it a center for trade commerce finance education and government thus it is a commercial and industrial port site Like during the Philippine Commonwealth the North Harbor was now developed for inter-island maritime shipping while the South Harbor was made for foreign trade There was limited use of the shipping vessels for berth and Anchorage the domestic vessels in the f Luneta